Reduction of allergenicity of litchi chinensis flowers pollen protein - Ranajit Kumar Shaha; Nitai Roy; G.Talukdar (2012)
Background: Allergy to pollen from gymnosperms is well documented in the west. The objective was to define the allergologic protein from Litchi chinensis (Litchi) pollen and conjugate the protein with polysaccharides by Maillard reaction to reduce the allergic effect of that protein. Methods: Total soluble proteins were extracted from the pollen of Litchi flower pollen and subjected to ammonium sulphate precipitation at 80% saturation. Pollen antigen from Litchi chinensis (Litchi) was prepared by gel cutting method and characterized by biochemical and designated by LFPP. The homogeneity of this protein was demonstrated by a single band on SDSPAGE. The protein then conjugated with galactomannan through Maillard Reaction. The resulting purified pollen protein and conjugated protein were administrered to the swiss albino mice as amount of 5.8mg/kg body weight. Results: The total protein was then separated on a 12% SDS-Polyacrylamide gel which revealed 5 bands between molecular weight range of 29 kDa and 69 kDa. Each band was recovered from the gel by electroelution and sent for skin tests. 28 kDa proteins was the only allergenic protein while others were not shown reactivity in patients. Intraperitoneal injection of the purified protein (LFPP) caused a significant rise in the levels of neutrophils (38-81%) and eosinophils (3-14%) compared to control (P<0.001) whereas conjugated protein caused only a 2% increase of both neutrophils and eosinophils level. On the other hand treatment with LFPPgalactomannan conjugate causes no such change in physical appearance with eosinophils and neutrophils level. Conclusion: The present study demonstrates that the protein extracted and purified from Litchi flowers pollen has been recognized as a new allergen from Bangladesh for the first time and the allergic effects can be reduced by conjugation with polysaccharides.